2018
DOI: 10.1038/s41467-018-05854-6
|View full text |Cite
|
Sign up to set email alerts
|

The tumor suppressor menin prevents effector CD8 T-cell dysfunction by targeting mTORC1-dependent metabolic activation

Abstract: While menin plays an important role in preventing T-cell dysfunction, such as senescence and exhaustion, the regulatory mechanisms remain unclear. We found that menin prevents the induction of dysfunction in activated CD8 T cells by restricting the cellular metabolism. mTOR complex 1 (mTORC1) signaling, glycolysis, and glutaminolysis are augmented by menin deficiency. Rapamycin treatment prevents CD8 T-cell dysfunction in menin-deficient CD8 T cells. Limited glutamine availability also prevents CD8 T-cell dysf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 68 publications
0
52
1
Order By: Relevance
“…18,34 Any condition causing even a modest variation in the cytosolic levels of aKG might affect different pathways, promoting either oncogenic or tumor suppressive responses: an increase of fatty acid biosynthesis or promotion of aberrant mammalian target of rapamycin 1 (mTORC1) activation ( Figure S3). [35][36][37] In addition, DLST mutation causing the loss of OGDH-complex nuclear-translocation capacity might lead to altered overall gene expression ( Figure S3). 38 The increased aKG to fumarate ratio in p.Gly374Glumutated tumors suggests that this variant leads to a disruption of OGDH complex activity.…”
Section: Discussionmentioning
confidence: 99%
“…18,34 Any condition causing even a modest variation in the cytosolic levels of aKG might affect different pathways, promoting either oncogenic or tumor suppressive responses: an increase of fatty acid biosynthesis or promotion of aberrant mammalian target of rapamycin 1 (mTORC1) activation ( Figure S3). [35][36][37] In addition, DLST mutation causing the loss of OGDH-complex nuclear-translocation capacity might lead to altered overall gene expression ( Figure S3). 38 The increased aKG to fumarate ratio in p.Gly374Glumutated tumors suggests that this variant leads to a disruption of OGDH complex activity.…”
Section: Discussionmentioning
confidence: 99%
“…In evaluating the role an altered metabolic environment plays in the process of modifying CD8+ T-cell function, we found that key metabolites, including lactate, had unexpected functions in the activation of CD8+ T cells, with multiple TCA metabolites stimulating the loss of CD62L. CD62L shedding from TCR activated CD8+ T-cells has been suggested to be mTOR and PI3K dependent ( Sinclair et al, 2008 ) and aKG-mediated activation of mTORC1 has been reported in multiple cell lines ( DeBerardinis et al, 2007 ; Durán et al, 2013 ; Villar et al, 2015 ), as well as in activated CD8+ T-cells ( Suzuki et al, 2018 ), suggesting that the metabolite-induced loss of CD62L may be mediated through mTOR activation. In addition, we found that lactate induces an effector profile and an overall increase in cytotoxic activity.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed in the previous section, elevated expression of CD38 on T cells inversely regulates glutaminolysis, a predominant pathway of yielding α-KG, which act as a co-factor of histone and DNA demethylases [13,135]. Recently, it has been reported that α-KG mediated H3K27 demethylation can be linked to the increased effector cytokines (IFN-γ and IL-2) production by mouse CD8 + T cell [137]. The study arouses the possible association of CD38 dependent metabolic rewiring as a critical cellular event regulating the epigenetic modification of T cells and hence their functional state.…”
Section: Metabolites Mediated Epigenetic Regulationmentioning
confidence: 91%